WORKSHOP PENCIPTAAN KARYA SENI RUPA ABSTRAKSI WAYANG MELALUI TEKNIK CETAK GELEMBUNG SEBAGAI STIMULUS KREATIVITAS BAGI ANAK USIA DINI (TK) - Zarkasi, Muh. Sofwan; Yulianto; Dite, Stri Agneyastra (Abdi Seni, 2024)
The community service entitled Workshop on the Creation of Wayang Abstract Artwork Through Bubble PrintingTechniques as a Stimulus of Creativity for Kindergarten Students (TK)” at KB TK AL-A’RAAF on Jl. Mangesti No.G9, Gentan, Baki, Sukoharjo, Central Java, is an artwork community service activity that answers partners’ needsregarding a stimulus strategy for fostering children’s creativity. This workshop is about creating wayang abstractionartwork using soap bubble print. This workshop activity provides a play space for children to have direct interactionafter two years reduced due to the COVID-19 pandemic situation. Through playing with colors and soapy waterwhere the bubbles are printed onto the media to form this wayang abstraction, students get playing time to growcreativity and interaction; apart from that, students are also brought closer to the richness of the Nusantara(Indonesian archipelago) traditions, namely wayang